PENERAPAN APLIKASI PELAPORAN SECARA DIGITAL UNTUK PENGAWAS PEKERJAAN DALAM RANGKA PENGENDALIAN PROYEK - Ernowo Ary Fibriyantoro; Nahar Afrizal (Universitas Quality, 2022)
One of the obstacles in construction supervision is the long distance of the project site. The results of the work progress report have not been maximized. This is due to the difficulty of obtaining data on the work that has been done. This job data makes it easier for service users to control work in the field, so that when problems occur in the field, they can be followed up immediately. So we need an easy work monitoring progress report format by utilizing technology. Development and implementation of e-report applications. Develop a Technical Team and instruct the preparation of data for application development and implementation of the implementation of digital reports. Coordination of e-report application development through the group with the technical team. Carry out Phase 1 Trial for application development. Socialization of the application of e-reports to Service Providers and Supervision. Carry out the Phase 2 trial of the application to improve the output. The Application Trial was carried out 2 times. Parties involved in the Office's internal Office Phase 1 Application Trial. The parties involved in the Phase 2 External Office Application Trial. The obstacle experienced was internet interference during field trials, each individual's understanding was different. The solution is to look for a signal in a certain area, using a provider with a good internet signal. The trial of the e-report application went well. This application is a prototype with features that can be used to compile project reports digitally. Short-term realization, namely the preparation of a Digital Daily Report Application and the realization of real-time and accurate digital project reporting. For the medium-term and long-term targets, namely the realization of android and web-based application development for construction supervision.